Influence of electrolyte temperature on corrosion Behavior of carbon steel pipe API 5L X52 and X70 . - Majda MOKHTARI; Aicha ZIOUCHE; Selma ATTABI; Hicham ELMSELLEM (University of Eloued جامعة الوادي, 2019)
In this study, electrochemical experiments were conducted to select the optimal electrolyte temperature to have excellent corrosion resistance in 0,1M hydrochloric acid using API X52 and X70 carbon steels. The temperature elevation effect was examined in the temperature range from 293- 323 K. The experiments showed that the corrosion current density was significantly lower when temperature increases and the aggressive solution effect is more important on X52 steel than X70 steel.
Intervention
Keywords: Keywords—corrosion; carbon steel; pipeline steel; temperature effect; acid solution.